DIDACTIC POTENTIAL OF PHYSICAL EDUCATION CLASSES IN PROVIDING PHYSICAL ACTIVITY OF ZVO QUARANTINE STUDENTS - Pavlos, Ruslan; Kuspish, Aleksandr; Nezgoda, Svitlana; Havrylenko, Mykola (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to the issue of physical activity of students of higher education institutions and the role of physical education in ensuring its proper level in quarantine. It is determined that the task of physical education in the new realities of distance education is the need to ensure students' understanding of the threats of lack of physical activity, as well as assistance by all possible means to compensate for its lack in their school day. The purpose of the study is to identify areas of the discipline "Physical Education" in ensuring the appropriate level of motor activity of students in quarantine. The research is based on the use of a set of general scientific theoretical methods: analysis, synthesis, systematization, generalization. The relationship between physical education, physical activity and student health has been proven. It is determined that the systematic motor activity of student youth is one of the determining factors of a healthy lifestyle. As a result, it was found that in order to increase the motor activity of the student, in conditions of quarantine restrictions, it is necessary to: teach students to study in quarantine; clearly define the values of motor activity in the student's life; to develop new methods of development of interests and motives to physical exercises of increase of motor activity in the conditions of quarantine; introduce new forms of distance physical education; to reorient the process of physical education in institution of higher education in the online format to educational and methodical with an emphasis on solving urgent problems of physical education due to quarantine; to introduce new forms of independent physical exercises; formation of the ability to independently use the means of physical education in quarantine; mastering the skills of a healthy lifestyle.